HUBUNGAN ASUPAN PROTEIN,SERAT DAN DURASI TIDUR DENGAN STATUS GIZI MAHASISWA S-1 ILMU GIZI - Dini Rachmadianti; Ikha Deviyanti Puspita (JURNAL RISET GIZI, 2020)
Background: Student are in a phase that can be classified as early adulthood or late adolescence at the developmental stage, namely the age of 18-25 years. Teenagers are a group that is vulnerable to environmental changes, specifically health and nutrition issues. Nutrition problems that are always faced by adolescents, namely the problem of multiple nutrition, namely lack of nutrition and obesity. one of the factors that influence nutritional status is protein intake, fiber and sleep duration Objective: To determine the relationship between protein intake, fiber intake and sleep duration with nutritional status of S-1 Nutrition student of Uiversitas Pembangunan Nasional Veteran Jakarta.Method: This study is an observational study with a cross sectional design. 46 students were selected for this study. Dietary intake (protein and fiber) was obtained by interview using 24h recall. Sleep duration was obtained using a sleep time questionaire. Nutritional status was collected by measuring body weight, height, upper arm circumference and ulna. Statistical analysis using the Chi-Square Test.Result: Most of the subjects had sufficient protein intake, less fiber intake and insufficient sleep duration. Most of the subjects had normal nutritional status (76.1%). there is no relationship between protein intake, fiber and sleep duration with nutritional status and nutritional status (p 0.05)Conclusion: adopting a healthy lifestyle by managing adequate sleep and balanced eating habits